2017
DOI: 10.1097/md.0000000000006364
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment hematologic markers as prognostic factors in patients with nasopharyngeal carcinoma

Abstract: Background:Pretreatment hematologic parameters of the inflammatory response, including lymphocyte, neutrophil, and platelet counts, neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio, and platelet-to-lymphocyte ratio, have emerged as prognostic factors for patients with cancer. This systematic review and meta-analysis aimed to summarize the association between the hematologic markers and prognosis of nasopharyngeal carcinoma (NPC).Methods:A systematic search of PubMed, Google Scholar, MEDLINE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…Meanwhile, in the study by An et al [10], patients with elevated N/L at diagnosis showed significantly worse DFS and distant metastasis-free survival, compared with patients with nonelevated N/L (47.2 vs. 73.7% and 59.2 vs. 85.1%, respectively). A recent pooled analysis summarized all these East Asian published articles and results confirmed that nasopharyngeal cancer patients with a higher N/L had both higher mortality risk and recurrence risk than those with a low N/L [15]. However, as authors declared, it should be noticed that, due to the limitation of included population, conclusions should be limited to East Asian population only.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in the study by An et al [10], patients with elevated N/L at diagnosis showed significantly worse DFS and distant metastasis-free survival, compared with patients with nonelevated N/L (47.2 vs. 73.7% and 59.2 vs. 85.1%, respectively). A recent pooled analysis summarized all these East Asian published articles and results confirmed that nasopharyngeal cancer patients with a higher N/L had both higher mortality risk and recurrence risk than those with a low N/L [15]. However, as authors declared, it should be noticed that, due to the limitation of included population, conclusions should be limited to East Asian population only.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a decreased platelet count represents severe liver cirrhosis and is a predictor of liver-related death in patients with HCC. 67,69 To utilize the data available from the literature, meta-analyses on the influence of LMR in HNSCC and those of hematologic markers in other histological types of head and neck cancer should be conducted. The effects of other hematologic markers and of markers in other histological types of head and neck cancer have also been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the surfeit amount of studies published, the prognostic value of the NLR in patients with head and neck cancer remains unclear, and even controversial . There are several meta‐analyses of the NLR in nasopharyngeal cancers only . To the best of our knowledge, this is the first meta‐analysis investigating the prognostic role of NLR in head and neck cancer in all sites.…”
Section: Introductionmentioning
confidence: 99%
“…8 There are several meta-analyses of the NLR in nasopharyngeal cancers only. 9,10 To the best of our knowledge, this is the first metaanalysis investigating the prognostic role of NLR in head and neck cancer in all sites. Therefore, our purpose in this study was to consolidate the published literature in order to clarify the relationship between the pretreatment NLR and the prognosis of patients with cancer in all sites of the head and neck.…”
Section: Introductionmentioning
confidence: 99%